Early precut sphincterotomy for difficult biliary access to reduce post-ERCP pancreatitis: a randomized trial - Mariani, Alberto; Di Leo, Milena; Giardullo, Nicola; Giussani, Antonella; Marini, Mario; Buffoli, Federico; Cipolletta, Livio; Radaelli, Franco; Ravelli, Paolo; Lombardi, Giovanni; D’Onofrio, Vittorio; Macchiarelli, Raffaele; Iiritano, Elena; Le Grazie, Marco; Pantaleo, Giuseppe; Testoni, Pier Alberto (Endoscopy, 2016)
Background and study aim: Precut sphincterotomy is a technique usually employed for difficult biliary cannulation during endoscopic retrograde cholangiopancreatography (ERCP) for the treatment of bile duct disease. It is a validated risk factor for post-ERCP pancreatitis (PEP), but it is not clear whether the risk is related to the technique itself or to the repeated biliary cannulation attempts preceding it. The primary aim of the study was to assess the incidence of PEP in early precut compared with the standard technique in patients with difficult biliary cannulation. Secondary aims were to compare complications and cannulation success. Patients and methods: In this prospective, multicenter, randomized, clinical trial, patients who were referred for therapeutic biliary ERCP and difficult biliary cannulation were randomized to early precut (Group A) or repeated papillary cannulation attempts followed, in cases of failure, by late precut (Group B). PEP was defined as the onset of upper abdominal pain associated with an elevation in serum pancreatic enzymes of at least three times the normal level at more than 24 hours after the procedure. No rectal indomethacin or diclofenac was used for prevention of PEP.Results: A total of 375 patients were enrolled. PEP developed in 10 of the 185 patients (5.4 %) in Group A and 23 of the 190 (12.1 %) in Group B (odds ratio [OR] 0.35; 95 % confidence interval [CI] 0.16 – 0.78). The incidence of PEP was significantly lower in the early precut group (10/185, 5.4 %) than in the delayed precut subgroup (19/135 [14.1 %]; OR 0.42, 95 %CI 0.17 – 1.07). There were no differences in biliary cannulation success rates, bleeding, perforation, and cholangitis. Conclusions: In patients with difficult biliary cannulation, early precut is an effective technique and can significantly reduce the incidence of PEP. Repeated biliary cannulation attempts are a real risk factor for this complication.